Turkey 2017 Clinical Practice Guidelines on recommendations for screning diagnosing and managing hepatitis C virus - Idilman, Ramazan; Baykam, Nurcan; Kaymakoğlu, Sabahattin; Tabak, Fehmi; Bahçecioğlu, Halil İ. and Bektaş, Ahmet and Bulut, Cemal and Günşar, Fulya and İnan, Dilara and Karaosmanoğlu, Hayat K. and et al. (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Idilman R, Baykam N; Viral Hepatitis Guidelines Study Group. Turkey 2017 Clinical Practice Guidelines on recommendations for screning diagnosing and managing hepatitis C virus. Turk J Gastroenterol 2017; 28(Suppl 2); S90-S93.